Curriculum Implementation Problems in 2013 Course of Islamic Religious Education Elementary School Mojokampung Bojonegoro - choirul anam (STAI Attanwir Bojonegoro, 2021)
This study aims to find out the Problems of Implementing the 2013 Curriculum in Elementary School Islamic Education Subjects, as well as to find out the school strategy of SDN Mojokampung Bojonegoro in overcoming the problems of learning PAI Curriculum 2013. This study used a qualitative descriptive approach, with data collection methods of observation, interviews and documentary. The data analysis technique is data reduction, data presentation and drawing a conclusion. While the data validity technique uses observation, triangulation, and peer checking through discussion. The results showed that: The problems of learning Islamic religious education K-13 at SDN Mojokampung Bojonegoro were not too prominent due to the application of appropriate learning methods, and supported by competent human resources. The success of PAI learning can run effectively if there is a synergy between all lines, both teachers, students and the local community.